Screening of Factors Affecting Biological Delignification Process of Oil Palm Trunk Using Local Oyster Mushroom (Pleurotus Ostretus) - N., Zainol (World Academy of Research and Publication, 2011)
Oil palm trunk, a lignocellulosic waste, contains high cellulose content. The removal of lignin is essential as lignin inhibits almost all reactions occur on cellulose. This study is about the usage of a local oyster mushroom (Pleurotus ostreatus) as an agent of delignification and the screening of various factors in order to achieve the highest amount of lignin removal. The software Design- Expert version 6.08 is used to determine the most relevant design for the screening process which leads to the method of two-level factorial design with seven parameters at 1/8 fraction. Sixteen runs were done for the purpose of studying the effect of temperature (20°C and 30°C), pH value (5 and 8), humidity (controlled by the presence of silica gel), light exposure, moisture (controlled by the volume of water added, which varies from 0.5 mL to 5.0 mL), the ratio of fungi to medium (1:2 and 1:10) and contact time (from 2 and 10 days) in which all the respective values were obtained from literature study. From the analysis, the main effects of the process are temperature, which contributes up to 32.20%, pH value, which contributes up to 10.08%, fungi to the medium ratio which contributes up to 8.82% and moisture content, which contributes up to 7.63%. This study also found that there are interactions between main effects, which are between temperature and pH value, and temperature and fungi to the medium ratio. These findings proved that each of the factors may affect one and another during the process